Mesenchymal Stem Cell Therapy in Ischemic Stroke: A Meta‐analysis of Preclinical Studies. Issue 6 (14th December 2017) - Sarmah, Deepaneeta; Agrawal, Vishal; Rane, Pallavi; Bhute, Shashikala; Watanabe, Mitsuyoshi; Kalia, Kiran; Ghosh, Zhumur; Dave, Kunjan R.; Yavagal, Dileep R.; Bhattacharya, Pallab
Abstract : Numerous preclinical studies have been carried out using mesenchymal stem cells (MSCs) therapy for ischemic stroke. The purpose of the present meta‐analysis is to review the quality of preclinical studies. In all, 4, 361 articles were identified, out of which 64 studies were included (excluding in vitro studies). The results were obtained across species, route, and time of administration, immunogenicity, and doses. The median quality score 4.90/10, confidence interval 95%, and large effect size were observed, which strongly supports the translation potential of MSC therapy for ischemic stroke.